(untitled) (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
Higher Education immersed in the process of digital literacy has the challenge of promoting its understanding and development in an inclusive way. "Educational and interactive Storytelling Video Library" is created, a repository of audiovisual, interactive and digital educational materials to improve executive functions, language and values through the methodology of E-Service-Learning and TICs. Materials created by university students to be implemented in the early childhood education stage and aimed at facilitating teaching work in a digital and inclusive society. Resulting in an educational environment that generates a network between University, School and Family where knowledge is shared and transferred.